Risk, uncertainty and decision making models - Merigó, José M. (Henry Stewart Talks, 2011)
Decision making concept, Decision making environments, DM under certainty, uncertainty and risk, Ordered weighted averaging, DM under uncertainty: alternatives and criteria, Additional DM models, Dealing with imprecise information, Interval numbers, Fuzzy numbers, Imprecise information criteria